Peran Keluarga Piara sebagai Katalisator Transmisi Budaya dan Akselerasi Adaptasi Mahasiswa KKN di Ambon - Difa, Taj Cyrila Aprila Syahda; Komariah, Siti; Abdullah, Mirna Nur Alia (LPPM Institut Pendidikan Nusantara Global, 2025)
This research aims to analyze the role of foster families as catalysts in the process of local cultural transmission and the acceleration of adaptation for students participating in the Twelfth National Community Service Program (KKN Kebangsaan XII) in Negeri Leahari, Ambon City. Using a qualitative approach with an ethnographic method, this study illustrates how the interactions between students and their foster families significantly enhance their understanding of local cultural values and promote deeper social integration. Data were collected through participant observation, in-depth interviews, and documentation, followed by thematic analysis. The findings reveal that the foster family system does not merely provide accommodation, but serves as a vital medium for the transmission of cultural values such as pela gandong, mutual cooperation, and the philosophy of hidup orang basudara or communal living. These families act as active agents of social integration by creating an emotionally supportive and culturally rich environment that accelerates students’ adaptation to their new surroundings. The close and affective interactions between students and their foster families facilitate deep cultural internalization, which strengthens the students' ability to engage in cross-cultural communication and collaboration. This research emphasizes that foster families play a strategic role in experiential social education and can serve as an effective model for enhancing intercultural relations in community engagement programs. Their involvement not only enriches the students’ learning experience but also contributes to the preservation and revitalization of local cultural heritage.